2014
DOI: 10.1007/978-3-319-10984-8_8
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Epileptic EEG Signals with Delay Permutation Entropy and Multi-scale K-Means

Abstract: Most epileptic EEG classification algorithms are supervised and require large training datasets, that hinder their use in real time applications. This chapter proposes an unsupervised Multi-Scale K-means (MSK-means) MSK-means algorithm to distinguish epileptic EEG signals and identify epileptic zones. The random initialization of the K-means algorithm can lead to wrong clusters. Based on the characteristics of EEGs, the MSK-means MSK-means algorithm initializes the coarse-scale centroid of a cluster with a sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Moreover, PE is more robust than the zero-crossing rate to the signal length, although both have relatively similar theoretically notions [10]. These characteristics make the PE an appealing tool used in a large number of real world signal and image processing applications [14][15][16]. PE-based approaches have been used in various studies, such as distinguishing noise from chaos [17], dependences between time series [18], and econophysics [19] and physiological applications [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PE is more robust than the zero-crossing rate to the signal length, although both have relatively similar theoretically notions [10]. These characteristics make the PE an appealing tool used in a large number of real world signal and image processing applications [14][15][16]. PE-based approaches have been used in various studies, such as distinguishing noise from chaos [17], dependences between time series [18], and econophysics [19] and physiological applications [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [10] demonstrated, by experimental results, that PE is able to identify epileptic seizures in EEG and intracranial EEG (iEEG). The same authors proposed an unsupervised multi-scale K-means (MSK-means) algorithm to distinguish epileptic EEG signals and to identify epileptic zones [11]. Mateos et al [12] developed a method based on PE to characterize EEG from different stages in the treatment of a chronic epileptic patient.…”
Section: Introductionmentioning
confidence: 99%
“…EEG signals contain significant features that detail both regular and irregular brain activities, particularly epileptic seizures. In addition, high-temporal-resolution EEG data from the scalp, spanning multiple input channels, can be acquired through distributed continuous sensing techniques [7]. Traditionally, diagnosing epilepsy through visual analysis of EEG recordings, both clinically and conventionally, is labor-intensive and prone to error, with varying consistency among experts, because of its heavy reliance on human expertise and skill [8,9].…”
Section: Introductionmentioning
confidence: 99%